Mengintegrasikan Kearifan Lokal dalam Pendidikan Tinggi Islam untuk Memperkuat Nilai-Nilai Harmoni d Toleransi - Muqoyyidin, Andik Wahyun (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study examines the integration of local wisdom into Islamic higher education as a means to enhance Islamic values and foster harmony and tolerance in diverse academic environments. The research is conducted at several universities in Indonesia, where Islamic studies programs actively incorporate local traditions and cultural practices into the curriculum. Utilizing a mixed-method approach, combining qualitative interviews with educators and students, as well as content analysis of the curriculum, the study aims to understand the impact of this integration on students’ moral development and intercultural awareness. Results indicate that the inclusion of local wisdom within the Islamic educational framework enhances students’ understanding of core Islamic values such as peace, mutual respect, and social responsibility. Furthermore, the findings reveal that these practices help to bridge cultural gaps between students from different backgrounds, promoting a more harmonious and tolerant academic environment. The conclusion suggests that Islamic higher education institutions should continue to leverage local cultural resources to enrich Islamic education and contribute to societal cohesion.